Climate change and the 2030 corporate agenda for sustainable development - Leonard, Liam; Gonzalez-Perez, Maria Alejandra (Bingley : Emerald Group Publishing Limited, 2016)
This volume explores the meaning of the Paris Climate Agreement 2015 for business; it analyses its challenges and implications, and establishes required actions by the private sector in order to reduce global warming and mitigating climate change effects. We bring together evidence-based, conceptual and theoretical contributions from a diverse set of geographical locations, and disciplinary backgrounds on the meanings, implications, opportunities and challenges for business around the planet in relation to climate change.
Prelims -- Climate change and the 2030 corporate agenda for sustainable development -- Climate change and the hospitality and tourism industry in developing countries -- Inseparable parts of sustainability: business, climate change, and integrated reporting -- Addressing climate change due to emission of greenhouse gases associated with the oil and gas industry: market-based regulation to the rescue -- Climate change and animal health risk -- Maldivian disaster risk management and climate change action in tourism sector: lessons for the sustainable development agenda -- The business case for climate change: the impact of climate change on Kenya's public listed companies -- Company policies to adapt climate change plan: a case study on Turkey -- Hidroays en case: building dams in Chile's Patagonia region -- Indonesia's forestry policy at a crossroads in the sustainable development approach: a case study on the forest moratorium, 20112014 -- Creation and shaping of the global solar photovoltaic (pv) market -- About the authors.
Includes bibliographical references.
Print version record
Keywords: Political Science -- Public Policy -- Environmental Policy; Climate change; Climatic changes -- Economic aspects